Regulatory patterns of testis and ovary maturation in largemouth bass (Micropterus salmoides) revealed by transcriptome profiling - Qingchun Wang; Siqi Lu; Jixiang Hua; Yifan Tao; Yan Zhuge; Wenhua Chen; Xuejun Duan; Jun Qiang (Aquaculture Reports)
Largemouth bass (Micropterus salmoides) is an economically significant farmed fish. It would be useful to understand its gametic maturation to establish effective breeding populations. We conducted histological analyses, transcriptome sequencing, and fluorescent in situ hybridization (FISH) analyses to detect differences in gene expression between ovaries and testes of sexually mature largemouth bass (6.5 months old). Analyses of differentially expressed genes and a gene set enrichment analysis identified 32 genes associated with gametic maturation (17 in ovaries; 15 in testes). Those in the ovaries included elovl1a, hsd17b12a, cidec, and acls5, encoding enzymes involved in lipid biosynthesis in stage III and IV oocytes; lrp13 and iars2, encoding proteins involved in yolk particle synthesis; and cpeb1b, cth1, and ccnb1, encoding proteins involved in the initiation and termination of meiosis to ensure oocyte maturation. The important genes in the testes were associated with the formation and assembly of microtubule structures. They included cfap161, spag6, iqub, enkur, tekt1, mns1, gas8, and ccdc40, encoding proteins involved in the regulation of the structural formation of sperm flagella; and lrguk, spef2, and tdrd5, encoding proteins involved in the initiation of spermatid assembly and maturation to form sperm — a critical stage in spermatogenesis. The transcriptome data and FISH results revealed high expression of dmrt1 in the extracellular matrix of spermatogonia cells, and of btg4 in the cytoplasm of stage IV oocytes. These two genes may serve as crucial regulatory factors in the maturation of testes and ovaries, respectively. Our findings offer insights into the mechanisms underlying gonad maturation in largemouth bass.